Health literacy and health promoting behaviors among inpatient women during COVID-19 pandemic - Ali Reza Yusefi; Eshagh Barfar; Salman Daneshi; Mohsen Bayati; Gholamhossein Mehralian; Peivand Bastani (BMC, 2022)
Abstract Background One of the leading health indicators during the COVID-19 crisis is health literacy and health-promoting behaviors. The present study aimed to investigate health literacy and health-promoting behaviors among women hospitalized during the COVID-19 pandemic in the southern part of Iran in 2020. Methods This descriptive-analytical study encompassed 465 women hospitalized and treated in none teaching hospitals affiliated with the Shiraz University of Medical Sciences. Data collection tools were the Health Literacy for Iranian Adults (HELIA) and Health Promoting Lifestyle Profile II (HPLP-II). The collected data were analyzed using descriptive and inferential statistical methods. Results The mean scores of the participants' "health literacy" and "health-promoting behaviors" were 64.41 ± 11.31 and 112.23 ± 16.09, respectively, indicating the poor level of health literacy and the average level of health-promoting behaviors. Moreover, there was a significant direct correlation between health literacy and health-promoting behaviors (P < 0.001, r = 0.471). Furthermore, all health literacy dimensions of comprehension (P < 0.001), accessibility (P < 0.001), reading skills (P < 0.001), evaluation (P = 0.002), and decision making and behavior (P = 0.003) were detected as the predictors of health-promoting behaviors. Further, statistically significant relationships were noticed between the mean score of health literacy with age (r =  − 0.327, P = 0.007), level of education (F = 3.119, P = 0.002), and place of residence (t = 2.416, P = 0.004) and between health-promoting behaviors with level of education (F = 3.341, P = 0.001) and marital status (F = 2.868, P = 0.02). Conclusion According to the findings, health policymakers should adopt national measures for educational planning to promote health literacy and support health-promoting behaviors to encourage women to adopt a healthy lifestyle.